1999
DOI: 10.1034/j.1600-0412.1999.780613.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of urinary incontinence and its influence on the quality of life in women from an urban Swedish population

Abstract: Although urinary incontinence was a prevalent condition, particularly among the elderly and had a negative influence on the quality of life, only a small number of women had sought medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
1
8

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 22 publications
(36 reference statements)
9
95
1
8
Order By: Relevance
“…Incontinence may be a cause of great discomfort, embarrassment and loss of self-confidence, and may interfere with daily life, general health, and the overall quality of life [1,2]. Incontinence may also lead to possible rejection on the part of a relative and may therefore be an important factor in the decision whether or not to institutionalize an elderly person.…”
Section: Introductionmentioning
confidence: 99%
“…Incontinence may be a cause of great discomfort, embarrassment and loss of self-confidence, and may interfere with daily life, general health, and the overall quality of life [1,2]. Incontinence may also lead to possible rejection on the part of a relative and may therefore be an important factor in the decision whether or not to institutionalize an elderly person.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern across the age range is not in accordance with previous work. In a study of women in Göteborg, Sweden, stress incontinence was more common than urge incontinence in women younger than 50 years of age, whereas in women 50 years of age or older, symptoms of mixed (concurrent stress and urge incontinence) or urge incontinence predominated [20]. Elving et al [21] have shown that the annual incidence (i.e., the rate of occurrence of new cases) of stress incontinence decreases, whereas that of urge incontinence increases in women 45 to 50 years of age compared with those 55 to 60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The total cost of care for persons with incontinence is estimated at USD 11.2 billion annually in the general community and USD 5.2 billion in nursing homes. The estimated prevalence rates for incontinence range from 3% in subjects aged 20–30 years to 53% in elderly patients [2, 3, 4, 5, 6, 7, 8, 9]. Refractory urge incontinence has been reported to account for 60–70% of all urge incontinence [10].…”
Section: Introductionmentioning
confidence: 99%